Long Non-Coding RNAs Associated with Ribosomes in Human Adipose-Derived Stem Cells: From RNAs to Microproteins - Bernardo Bonilauri (MDPI AG, 2021)
Ribosome profiling reveals the translational dynamics of mRNAs by capturing a ribosomal footprint snapshot. Growing evidence shows that several long non-coding RNAs (lncRNAs) contain small open reading frames (smORFs) that are translated into functional peptides. The difficulty in identifying bona-fide translated smORFs is a constant challenge in experimental and bioinformatics fields due to their unconventional characteristics. This motivated us to isolate human adipose-derived stem cells (hASC) from adipose tissue and perform a ribosome profiling followed by bioinformatics analysis of transcriptome, translatome, and ribosome-protected fragments of lncRNAs. Here, we demonstrated that 222 lncRNAs were associated with the translational machinery in hASC, including the already demonstrated lncRNAs coding microproteins. The ribosomal occupancy of some transcripts was consistent with the translation of smORFs. In conclusion, we were able to identify a subset of 15 lncRNAs containing 35 smORFs that likely encode functional microproteins, including four previously demonstrated smORF-derived microproteins, suggesting a possible dual role of these lncRNAs in hASC self-renewal.